PROPOSED IMPROVEMENTS OF SEMINAR BAG PRODUCTION SYSTEM TO MINIMIZE DELAYS IN PRODUCT DELIVERY (CASE STUDY IN CV. ABC) (The Indonesian Journal of Business Administration, 2019)
CV ABC is a firm involved in the production of bags in Bandung. CV ABC always strives to deliver the highest quality products and on-time delivery service in satisfying customer wishes. One product with the highest manufacturing demand on CV ABC is the seminar bag. In 2018, the seminar bag became the product with the highest demand but became the product that caused the company's biggest loss. The business encountered a reduction in profit Rp 77.934.000 due to late shipment of the product. Based on the issues, Current Reality Tree is used to define the key factors that cause delays in the product's shipment that lead the business to lose. Then it was discovered that no procurement plans, no production planning, no standard processes, no resource management and poor design facilities caused the delay. After understanding the key factors that cause delays in the product's shipment, alternative solutions are suggested. Proposed alternative solutions are forecasting for core suppliers, selecting new suppliers using Analytical Hierarchy Process method, determining worker demands, improving facilities layout, designing Standard Operating Procedures and recruitment processes, and combining all alternative alternatives. Then, comparison is created between alternative solutions that contain the total loss decrease and the solution's effectiveness. The discussion was performed with CV ABC to find the best alternative solution. The findings of the discussion show that the business selecting the best alternative solution for the short term that will be implemented is to add the number of workers. The addition of workers can decrease losses by Rp 37.140.000 with an effectiveness rate of 75 percent. The company then selects the combination of all alternative alternatives for the long-term implementation plan.Keywords:  Current Reality Tree, Effectiveness, Loss Reduction, On Time Delivery, Seminar Bag